Approach to the treatment of trichomoniasis associated with sexual transmitted infections - Э. М. Айзятулова (Publishing House TRILIST, 2019)
In recent years, mixed infection (trichomonas, gardnerella, chlamydia, mycoplasma, yeast-like fungi) is often found and is insensitive to antibacterial drugs. Therefore after treatment, the inflammatory process for a long time can be maintained by pathogenic microorganisms, which must be considered when prescribing therapy to such patients. The main decisive factor in the treatment of mixed urogenital infections is the appointment in the complex therapy of effective antibacterial drugs of a wide spectrum in sufficient daily doses and duration, that is allows obtaining positive results of treatment in most patients. Objective of the study. Analyze in women the anamnestic data and clinic of trichomoniasis associated with other sexually transmitted infections. Develop a comprehensive method for the treatment of trichomoniasis and concomitant urogenital infections. Materials and methods. Study include 31 women aged from 20 to 31 years. At examination along with trichomonads a concomitant urogenital infection (gardnerella, chlamydia, mycoplasma, yeast-like fungi) was detected in the patients. Diagnosis was carried out using standard techniques. In case of a mixed infection (trichomonas, gardnerella, chlamydia, mycoplasma, yeast-like fungi), antiprotozoal drugs were prescribed from the 1st day of treatment. After antiprotozoal treatment antimicrobials with a broad spectrum of action were prescribed from the 11th day of treatment. In the presence of a candidal infection from the 1st day of treatment an antifungal drug was used. Results. Analysis of the therapeutic efficacy of the proposed complex treatment of trichomoniasis and concomitant urogenital infection showed clinical recovery in the majority of patients. This was evidenced by the disappearance of subjective clinical symptoms, objective inflammatory changes in the mucous membrane of the genital organs, and the negative results of laboratory studies after completion of the course of treatment. Conclusion. The proposed comprehensive treatment of women with trichomoniasis associated with other sexually transmitted infections makes it possible to increase the effectiveness of therapy, promotes the elimination of pathogens and clinical recovery in most patients.